Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300745
|View full text |Cite
|
Sign up to set email alerts
|

Should I Agree?

Abstract: Obtaining meaningful user consent is increasingly problematic in a world of numerous, heterogeneous digital services. Current approaches (e.g. agreeing to Terms and Conditions) are rooted in the idea of individual control despite growing evidence that users do not (or cannot) exercise such control in informed ways. We consider an alternative approach whereby users can opt to delegate consent decisions to an ecosystem of third-parties including friends, experts, groups and AI entities. We present the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Suggested responses target every aspect of the consent process, ranging from technical solutions such as reducing the number of decisions by applying pre-defned policies [13] and making privacy policies more accessible [27], through to re-framing consent as a means of informing users, rather than just a disclosure exercise [28] and integrating practices from BDSM communities such as periodically checking in to see if interactions are meeting users' expectations [44]. Others have explored allowing users to delegate consent decisions to third parties, although found that around 50% of users still wished to make decisions themselves [34].…”
Section: Consent In Human-computer Interaction and Privacy Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggested responses target every aspect of the consent process, ranging from technical solutions such as reducing the number of decisions by applying pre-defned policies [13] and making privacy policies more accessible [27], through to re-framing consent as a means of informing users, rather than just a disclosure exercise [28] and integrating practices from BDSM communities such as periodically checking in to see if interactions are meeting users' expectations [44]. Others have explored allowing users to delegate consent decisions to third parties, although found that around 50% of users still wished to make decisions themselves [34].…”
Section: Consent In Human-computer Interaction and Privacy Regulationmentioning
confidence: 99%
“…An alternative arrangement would be to have tools run by consumer advocacy groups or nonprofits to foster trust, although the locked-down nature of current VA platforms would make this difficult. Prior work suggests that alongside competence, perceived intentions and moral integrity of third parties are important factors affecting peoples' trust in delegated consent decisions [34]. It is unfortunate that the GDPR does not easily allow for this kind of automated decision making to alleviate consent fatigue, but the vested interests of platforms in collecting data would make this a difficult area to effectively regulate.…”
Section: Reducing the Number Of Consent Decisionsmentioning
confidence: 99%
“…Social cues and expert recommendations can have a significant impact on users' decisions [11]. Furthermore, users have varied preferences and acceptance of different sources [33] and these sources have inherent biases. Because of this, a well-designed PPA should allow users to choose preferred sources and should offer both crowd-sourced recommendations and recommendations from authoritative sources.…”
Section: Designing the Information Analysis Functionmentioning
confidence: 99%
“…To the contrary, our findings suggest that privacy may not even feature as part of people's reasoning in circumstances where they provide consent. In that case, what of solutions that automatically recommend [63] or delegate responsibility for making consent decisions to a third party (trust proxy) more informed on the matter [78]? We would argue that these kinds of approaches take for granted the notion of consent as a valid and ethical starting point for ensuring privacy.…”
Section: Discussionmentioning
confidence: 99%